2016
DOI: 10.5507/ag.2016.006
|View full text |Cite
|
Sign up to set email alerts
|

Differences in pre-planned agility and reactive agility performance in sport games

Abstract: in the shortest possible time, similarly to cyclic speed, however, without defining the direction of movement (Harman & Garhammer, 2008). In fact, this issue is much more complex, since speed of movement is not constant during the whole length of trajectory of movement and thus it can be divided into several phases: acceleration, maintaining maximum speed and deceleration (Plisk, 2008). Agility is most frequently defined as a fast change of direction of movement (Altug, Altug, & Altug, 1987). It can adopt vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
(15 reference statements)
0
27
0
4
Order By: Relevance
“…In the current study, we found that sport type does not affect the RA performance or associated measures. In studies performed by Šimonek, Horička, and Hianik [ 22 ], there was no difference in the horizontal reactive agility between basketballers, volleyballers, and soccer players aged 15–16 years. Therefore, the RA measured using the Five-Time Shuttle Run to Gates test is relevant to various team sports, including volleyball, handball, and basketball.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found that sport type does not affect the RA performance or associated measures. In studies performed by Šimonek, Horička, and Hianik [ 22 ], there was no difference in the horizontal reactive agility between basketballers, volleyballers, and soccer players aged 15–16 years. Therefore, the RA measured using the Five-Time Shuttle Run to Gates test is relevant to various team sports, including volleyball, handball, and basketball.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive agility (RA), a whole-body movement that requires a change in velocity or direction in response to a non-planed external stimulus, reflects components related to visual sensorimotor processing, as well as representing an essential aspect of motor performance based on an energetic background [19][20][21]. It is generally accepted that agility in sports games is important to optimally prepare players across various stages of training [22,23]. In our opinion, reactive agility tasks directly reflect athletes' visuomotor processing of important conditions for team sports.…”
Section: Introductionmentioning
confidence: 99%
“…Performance in basketball depends on many factors, with the most important one being players’ somatic build, as well as technical, tactical, motor, physiological, and psychological preparation. A basketball coach must supervise balanced development of players, i.e., physique, visual and motor coordination improvement and development of necessary motor abilities, considering evolutionary processes connected with the pace of growth and maturation of players [ 1 , 2 , 3 ]. In basketball, an individualized approach and making anthropometric diagnoses are basic elements of the selection process and of developing a long-term sports career.…”
Section: Introductionmentioning
confidence: 99%
“…Other findings compared agility and reactive agility comparing the results of the Illinois Agility Test and Fitro Agility Check. The results showed that in Illinois Agility Test the content of the test is well known and the agility parameters are evasive compared with the Fitro Agility Check that is more spontaneous and require the sportive to decision making in short period of time (Simonek, Horicka, & Hianik, 2016). Those findings are also supported by another opinion that decision-making process in sport games is extremely important and they determine on the speed of realisation of the motor task to a great measure (Spasic, Krolo, Zenic, Delextrat, & Sekulic, 2015).…”
Section: Discussionmentioning
confidence: 99%